A Classification Method of Music Style Based on Text Mining and Neural Network - Jianfeng Zhang; Jin Wang (Dianxin kexue)
In terms of the confusion of music style ambiguous relationships caused by artificial classification and the problem that some songs cannot be classified into the proper style，the emotion of songs based on their lyrics to classify their belongings was analyzed.BP neural network was used to establish a music style forecast model and then a reasonable proof of the theory and derivation was made.This experiment use MATLAB as a modeling tool and determine the training parameters according to its characteristics，and then extract 10% from dataset to test.This approach shows that theoretical results and data simulation results agree well with the accuracy rate reached about 80%.